Exploration and Exploitation as Knowledge Management Strategic Approaches in Saudi Arabian SMEs - Azyabi, Naief; Fisher, Julie (ACIS, 2014)
This paper reports on a study of Saudi Arabian SMEs capabilities towards exploration and exploitation with respect to knowledge management (KM), in particular the association between the business strategic approach and decisions on exploration and exploitation. The Miles and Snow typology (prospectors, defenders and analysers) was used to investigate the business strategic approach. The study used a mixed methods approach involving a survey and interviews. The research found that the exploitation orientation was dominant among SMEs for many reasons including their focus on day-to-day activities and their limited resources which often prevented them from exploring new knowledge or applying new ideas. The decisions on exploration and exploitation were affected by knowledge sources and the breadth of the knowledge base. SMEs with a narrow knowledge base were unable to absorb external knowledge and apply it within their organisation. The outcomes of the research provides further insights into SMEs’ KM strategies.